2020
DOI: 10.1055/a-1302-0368
|View full text |Cite
|
Sign up to set email alerts
|

Regionale Verteilung der Cochlea-Implantat (CI)-versorgenden Einrichtungen in Deutschland

Abstract: ZusammenfassungDie Versorgung von Patienten mit einer hochgradigen Schwerhörigkeit oder Taubheit mit einem Cochlea-Implantat (CI) stellt heute in Deutschland einen Standard dar. Umso überraschender ist es, dass kaum Daten zur aktuellen Anzahl der CI-versorgenden Einrichtungen (CI-Kliniken) und zu deren geografischer Verteilung existieren. Der Selbsthilfeverband Deutsche Cochlea Implantat Gesellschaft (DCIG) e. V. und die Deutsche Gesellschaft für Hals-Nasen-Ohrenheilkunde, Kopf- und Halschirurgie (DGHNO-KHC) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In a survey conducted in 2020 by the DGHNO-KHC in collaboration with the patient self-help group ( Deutsche Cochlea-Implantat Gesellschaft , DCIG), 70 of 170 ENT hospitals existing in Germany stated that they perform CI treatment. It must be noted that the number of hospitals participating in this survey was not complete, so that the authors assume a number of approximately 100 hospitals offering CI care [ 14 ]. Against this background, the number of hospitals (i.e., 75) that agreed to participate in the registry is even more impressive, as it obviously already corresponds to the majority of CI hospitals in Germany.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey conducted in 2020 by the DGHNO-KHC in collaboration with the patient self-help group ( Deutsche Cochlea-Implantat Gesellschaft , DCIG), 70 of 170 ENT hospitals existing in Germany stated that they perform CI treatment. It must be noted that the number of hospitals participating in this survey was not complete, so that the authors assume a number of approximately 100 hospitals offering CI care [ 14 ]. Against this background, the number of hospitals (i.e., 75) that agreed to participate in the registry is even more impressive, as it obviously already corresponds to the majority of CI hospitals in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to the development of the CI guideline and the CI white paper for structuring the CI care process, an independent certification process for quality assurance of CI care was subsequently introduced in Germany [ 9 ]. As early as in 2016, after intensive discussion, the Executive Committee of the DGHNO-KHC made the decision to participate in the further development of quality control of CI care in a scientifically oriented manner.…”
Section: Methodsmentioning
confidence: 99%
“…Considering already existing surveys on the density of care in Germany, there is an earlier work addressing this issue. In the survey initiated by the DGHNO-KHC in 2020 [ 14 ], all 170 ENT hospitals in Germany existing at that time were asked about the provision of CI care. In this survey, 70 hospitals indicated that they offered CI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Germany can be considered as an example in this regard. Although at least 70 hospitals in Germany provide CI care and a CI CPG has already existed since 2001, the national CI registry is currently only in the implementation phase [ 19 , 20 ]. Other countries where there are currently efforts to establish a CI registry are Great Britain and Belgium.…”
Section: Discussionmentioning
confidence: 99%